(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract:This article discusses the common causes of grammatical confusion among English learners, especially at beginner and intermediate levels. It explains the main areas where learners often struggle—such as verb tenses, articles, prepositions, and word order—and offers insight into how these difficulties can be addressed in both teaching and self-study. The article also explores the impact of native language interference and highlights practical methods to overcome grammar-related challenges. Annotatsiya: Ushbu maqolada ingliz tilini o‘rganayotganlar orasida uchraydigan grammatik chalkashliklarning asosiy sabablari tahlil qilinadi. Ayniqsa, fe’l zamonlari, artikllar, predloglar va so‘z tartibi kabi sohalarda yuzaga keladigan qiyinchiliklar yoritilgan. Shuningdek, ona tilining ta’siri va grammatik xatolarni kamaytirish uchun samarali o‘qitish hamda o‘z-o‘zini o‘rgatish usullari tavsiya etiladi.